Normative and Perceived Need for Treatment of Malocclusion among Malaysian Adolescents - Zamzuri, S.Z.M.; Razak, I.A.; Esa, R. (Penerbit Universiti Kebangsaan Malaysia, 2014)
In practice, the need for orthodontic care is often determined by normative need. However, in reality, a person’s decision to seek orthodontic treatment is dependent on multiple factors. The aim of this study was to determine the association between normative and perceived need for orthodontic treatment among Malaysian adolescents. This is a cross-sectional study involving 700 school children aged 13-14 years in Jempol District, Negeri Sembilan, Malaysia. The Dental Health Component (DHC) and Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN) were used to assess the normative need. The children’s perceived need was obtained by matching the appearance of their anterior teeth with the photographs on the AC scale. The normative need according to the DHC was 27.1% while the AC indicated 21.9%. Only 3.2% of the schoolchildren perceived that they needed treatment. There was a significantly high correlation between the DHC and AC scores of the dentist (Spearman r s = 0.89, p<0.01). However, the correlation between the AC of dentist and AC score of the children was weak (Spearman r s = 0.39, p<0.01). No significant differences were observed for need of orthodontic treatment among gender and ethnicity according to the DHC and AC of dentists as well as AC of children (p>0.05). The findings from this study support the importance of considering the use of perceived need in prioritizing orthodontic treatment especially because of the shortage of orthodontic services in the country.